Statutory and Judicial responses to the Problem of Access to Government Information - SINGLETON, Constance Y. (Institutional Knowledge at Singapore Management University, 1979)
The tremendous growth of government occasioned by greater involvement in the social and economic life of the nation has been the cause of many concerns. Two perennial concerns have been the extent to which the government can prevent public access to information on the basis of which policies and decisions are made and the possibility for misuse by the government of information private to individuals or business firms. This article focuses on federal statutory responses to these issues. The legislative intent has usually been praiseworthy but the resulting statutes, especially as they have been interpreted by the courts, have often been mutually inconsistent, even to the point of being ironic. This article also briefly considers the recent case of Houchins v. KQED, Inc.,I in which the Court, by a narrow margin, rejected the argument that the first and fourteenth amendments mandate at least some access to information within the control of the government. The decision in Houchins and similar cases make the statutory responses to problems of access especially important.